2006
DOI: 10.1007/s11145-006-9031-0
|View full text |Cite
|
Sign up to set email alerts
|

Literacy ability and phonological processing skills amongst dyslexic and non-dyslexic speakers of Arabic

Abstract: This paper investigates the relationship between phonological processing and reading ability amongst grade 4 and grade 5 Arabic speaking children in Egypt. In addition to measuring reading level, the study assessed the children's ability to identify rhymes, delete individual phonemes from words, retain and manipulate sequences of digit names and rapidly access verbal labels. Further literacy and literacy-related tasks required children to decode novel letter strings, to distinguish similar words, to identify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 19 publications
11
64
0
Order By: Relevance
“…However, there were no significant differences in PB as a result of grade level. These findings are consistent with other studies of Arabic [10], [12]. The results also reflect similar finding on English language [13], [14].…”
Section: Discussionsupporting
confidence: 93%
“…However, there were no significant differences in PB as a result of grade level. These findings are consistent with other studies of Arabic [10], [12]. The results also reflect similar finding on English language [13], [14].…”
Section: Discussionsupporting
confidence: 93%
“…For example, Elbeheri, Everatt, Mahfoudhi, Abu-Diyar and Taibah's (in press) orthographic measure predicted variability in the comprehension fluency over-and-above that predicted by phonological measures in older mainstream children (grades 4 and 5) but not in the younger grades (2 and 3). This influence may not be due simply to greater literacy exposure since children with literacy learning problems (dyslexia) also show this influence of orthography (see also Elbeheri & Everatt, 2007). The finding that the influence of orthographic processing is explained by phonological processing measures in the younger cohort but not in the older groups is consistent with several models of reading acquisition that were developed for orthographies other than Arabic.…”
Section: Orthographic Influencessupporting
confidence: 69%
“…Given this, it is hardly surprising to find that investigations of phonological processing and its role in reading development, have been a focus for many studies looking at the relationship between language and literacy, including those investigating Arabic literacy development. Consistent with the importance of phonological processing in literacy development, many have found that phonological measures (when applied in the standard variety, i.e., the variety learned at school) are related to reading and spelling skills in Arabic (see Abu-Rabia, Share, & Mansour, 2003;Al-Mannai & Everatt, 2005;Elbeheri & Everatt, 2007). However, Elbeheri et al (2006) also argue that further research is necessary to allow firm conclusions to be made given that variations from predictions based on English language models have been identified.…”
Section: Phonological Processesmentioning
confidence: 91%
“…They are also written with slight difference according to the preceding letter (Ibrahim, 2013). In addition to the diacritics for the three short vowels, there are additional reading signs that contribute phonology to the Arabic alphabet (for a summary, see Abu-Rabia, 2001, 2002Elbeheri & Everatt, 2007;Taouk & Coltheart, 2004). Thus, the complexity of the visual information which is expected from the reader to process demands heavy reliance on visual processing besides the phonological processing.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%